Imagining justice for Syria water always finds its way - Van Schaack, Beth (Oxford University Press, 2020)
The situation in Syria poses an acute-some might say existential-challenge to the international community's commitment to justice and accountability. It also marks the abject failure of the international system of peace and security erected in the post-World War II period. The Security Council has been almost entirely incapacitated by the propensity of Russia to wield its veto against nearly every coercive measure of any consequence, including legal accountability, that might be imposed on the regime of Syrian President Bashar Al-Assad. As a result, other actors, within and outside of the United Nations, have endeavored to find inventive ways around this geopolitical impasse. This forced creativity has generated a number of innovative institutions, legal arguments, and investigative techniques aimed at advancing justice and accountability for Syria, wherever possible. This book catalogues the many obstacles to this pursuit of justice for Syria and analyzes ways today's justice entrepreneurs have worked to find paths around them. The book's subtitle-Water Always Finds Its Way-reflects this idea that the quest for justice is inexorable. Just as water eventually finds its way through cracks and around obstacles, even if at a trickle, so too will justice. Virtually every international crime that forms part of the international penal code-a mélange of customary international law and treaty provisions-has been committed in and around Syria. The Syrian people have witnessed and been subjected to deliberate, indiscriminate, and disproportionate attacks; the misuse of conventional, unconventional, and improvised weapon systems; industrial-grade custodial abuses in a vast network of formal and informal prisons; unrelenting siege warfare; the denial of humanitarian aid and what appears to be the deliberate use of starvation as a weapon of war; sexual violence, including the sexual enslavement of Yezidi women and girls trafficked from Iraq and the sexual torture of detained men and boys; and the intentional destruction of irreplaceable cultural property. Thousands of Syrians are missing, many of them victims of enforced disappearances. Even children are not spared. The long-standing taboo against the use of chemical weapons has been repeatedly flouted in ways that constitute a double violation of IHL: the use of a prohibited weapon to target civilians. And, the sectarian nature of the violence has raised the specter of genocide against ethno-religious minorities. Indeed, then-Secretary of State John Kerry announced in 2016 that ISIL was committing genocide against a number of minority groups in Syria and Iraq. Violence in the region has contributed to the biggest exodus of refugees since World War II"--